KEGIATAN LAKI-LAKI DI DAERAH ALIRAN SUNGAI (DAS) UNDA KABUPATEN KLUNGKUNG - Ida Bagus Astika Pidada; I Nengah Mileh; Ni Ketut Sukiani (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2024)
The Unda River Watershed is familiar to the East Bali area, especially in Klungkung Regency. The people in Klungkung are called Tukad Unda or Yeh Unda for this river. The Unda River Watershed is sourced from 7 (seven) rivers so it almost never dries throughout of the year, namely: (1) Telagawaja River, (2) Barak River, (3) Sah River, (4) Mangening River, (5) Masin River, (6) Krekuk River, and (7) Bajing River. The method of this research is applied qualitative method. The data collection is taken from primary data and secondary data collection. Then, the data is reduced, presented and collected. Therefore, many people do the activities in this river, especially for men. The activities in this river, such as: looking for a livelihood like opening a vehicle washing business, opening a stone and concrete crafts business, opening a rafting business and restaurant, as well as digging c. Besides that, this river is also used by men for religious ceremonies and fishing activities for fun or entertainment. This indicates that the Men in the Unda River Watershed is applied an active role in opening up existing opportunities to develop the business in the future.